Analysis of Serum Ghrelin Levels and BMI in Obese and Non-Obese Subjects - Patachna Junita; Ruland DN. Pakasi; Liong Boy Kurniawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Obesity is excessive body fat and was associated with the importance of metabolic and endocrine problems in somatotropic secretion in functional obesity. Ghrelin is an acylated peptide hormone produced by the stomach, which is a mediator of the growth hormone secretory receptor. The activity of ghrelin stimulates the release of growth hormone, and appetite and stimulates the metabolism of carbohydrates. Circulating ghrelin levels in healthy people increase during fasting and decrease after meals. This study aims to analyze the difference in ghrelin levels among obese and non-obese subjects. A cross-sectional design research was conducted in August 2022. The samples consisted of obese and non-obese subjects based on Body Mass Index (BMI). Ghrelin levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA) method. The data were statistically analyzed using the Mann-Whitney and Spearman tests. p<0.05 was reported significant. The samples consisted of 80 obese and non-obese subjects, 39 males and 41 females. There was no difference in ghrelin serum levels in the obese group (1.45±2 ng/mL) compared to the non-obese group (0.67±0.25 ng/mL) with p =0.233 (p>0.05). There was a positive correlation between ghrelin levels and BMI (r=0.247). There was no difference in ghrelin levels between the obese group and the non-obese group, and there was a positive correlation between ghrelin levels and BMI. A higher BMI would lead to higher ghrelin levels.